Productivity and economics of different agri-silvi-horti systems under drip irrigation - KAUSHIK, N; KUMARI, SUSHIL; SINGH, SURENDER; KAUSHIK, J C (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted in two years old fruit and tree species namely shisham (Dalbergia sissoo) + aonla (Embilica officinalis), shisham (D. sissoo) + guava (Psidium guajava), khejri (Prosopis cineraria) + aonla (E. officinalis) and khejri (P. cineraria) + guava (P. guajava) during 2007-08 and 2008-09 planted at a spacing of 6m×6m. The crop sequences, viz. ridgegourd (Lifa acutangula) - tomato (Solanum lycopersicum), moongbean (Vigna radiata) - fallow and cluster bean (Cyamopsis tetragonoloba) - fallow were raised in the interspaces of the trees. Ridgegourd and tomato were raised with drip irrigation, while moongbean and cluster bean were raised as rainfed. The trees and crops were subjected to three drip irrigation treatments, viz. T1 (100% ETc), T2 (70% ETc) and T3 (40% ETc) with three replications per treatment. Yield of intercrops was not affected by the different silvi-horti systems. The irrigation treatments influenced the yield of crops and growth of trees. Maximum yield (39323 kg/ha) of tomato and growth of trees was recorded under 100% replenishment of water except in case of shisham, where maximum height (803.0 cm), diameter (15.4 cm) and crown spread (550 cm2) was recorded under 70% replenishment of water after 48 months of plantation. Maximum irrigation water use efficiency (19.34 g/l) was recorded for ridgegourd under 40% replenishment of water when grown in association with khejri + aonla. Intercropping of tomato and ridgegourd with khejri + guava was found most remunerative with maximum NPV, BC ratio and net returns after sole cropping.